Supply Chain Sustainability as a Mediator of Sustainable Performance in Indonesian Logistics SMEs - Ferdy; Stefanus Kaihatu; Timotius Febry Christian (Jurnal Manajemen Industri dan Logistik, 2026)
This study investigates supply chain sustainability as a mediating mechanism transforming organizational antecedents into sustainable performance outcomes among Indonesian logistics small and medium enterprises (SMEs). Drawing on stakeholder theory and resource-based view, we develop and test a mediation model using data from 284 Indonesian logistics SMEs across five geographic regions. Partial least squares structural equation modeling with 5,000 bootstrap resamples examines relationships between top management commitment, technology investment, human employee engagement, supply chain sustainability, and sustainable performance. Results reveal complete mediation patterns where supply chain sustainability fully mediates relationships between organizational antecedents and sustainable performance.